If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -4x = -15 + 2x Solving 12 + -4x = -15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -4x + -2x = -15 + 2x + -2x Combine like terms: -4x + -2x = -6x 12 + -6x = -15 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -6x = -15 + 0 12 + -6x = -15 Add '-12' to each side of the equation. 12 + -12 + -6x = -15 + -12 Combine like terms: 12 + -12 = 0 0 + -6x = -15 + -12 -6x = -15 + -12 Combine like terms: -15 + -12 = -27 -6x = -27 Divide each side by '-6'. x = 4.5 Simplifying x = 4.5
| x^6=1296 | | 5y-8x=8x | | f(x)=x+4(2x+1)8x^2+4 | | 4-6(2x-3)+1=3+7(5-x) | | 2-8m=14-3+8m | | t^2-24=2t | | k^2-20k-35=0 | | g(x)=x+7(2x)2x+14 | | 11/18x^2-7x-56=0 | | 0.6111x^2-7x-56=0 | | 4(x+2)=3(2x-(6-x)) | | 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x | | 2x+x=59 |